Judge knot : politics and development in international investment law - Tucker, Todd N. (Anthem frontiers of global political economy., 2018)
'Judge Knot' explores the biggest and the most controversial success story in international law: investor-state dispute settlement, or ISDS, and asks what makes the system tick and what it means for the future of democracy and development.